Alternative Dispute Resolution of People's Mining (Study in West Lombok Regency) - Ari Ade Kamula; Baiq Salma Widiana (Magister of Law, Faculty of Law, University of Mataram, 2021)
The Law on mineral and coal mining provides opportunity to carry out mining business activities.Â To do mining out by the people by using the people suggest. In practice, causes problem in the form of vertical and horizontal conflicts society in west Lombok district. people's mining conflict were caused by uncontrolled mining activities and mining land ownership dispute. In the above issues, alternatives are needed in resolving disputes that occur, so that conflicts that occur can be resolved. This study empirical law research to understand that the law is not only a normative legal regulation. The data in this study were obtained from literature studies and field research, using a sociological juridical approach, the result prove that alternative mechanism of settlement of mining disputes based on the good faith of the parties in the conflict, to reach an agreement that can provide a sense of justice.